Validity and reliability of inertial measurement system for linear movement velocity in flywheel squat exercise - Maroto-Izquierdo, S.; Nosaka, K.; Alarcón-Gómez, J.; Martín-Rivera, F. (Sensors, 2023)
The aim of this study was to examine the validity and reliability of an Inertial Measurement System integrated into a secondary pulley (IMS) for determining linear velocity during flywheel squat exercises. Thirty-one male participants who were highly experienced in a flywheel resistance exercise training performed flywheel squat exercises with three incremental loads, and mean velocity (MV), mean propulsive velocity (MPV) and max velocity (Vmax) of the exercises were simultaneously recorded with a validated linear encoder and the IMS, in two different sessions. Validity was analyzed using ordinary least products regression (OLP), Lin`s concordance correlation coefficient (CCC), and Hedge`s g for the values from the linear encoder and the IMS. Test-retest reliability was determined by coefficient of variation (CV), Intraclass correlation coefficient (ICC), and standard error of measurement (SEM). Results showed a high degree of validity (OLP intercept = -0.09-0.00, OLP slope = 0.95-1.04, CCC = 0.96-0.99, Hedge`s g < 0.192, SEM = 0.04-0.08) and reliability (CV < 0.21%, ICC > 0.88, SEM < 0.08). These results confirm that the IMS provides valid and reliable measures of movement velocity during flywheel squat exercises.